2018
DOI: 10.3390/ijms19123779
|View full text |Cite
|
Sign up to set email alerts
|

Relating Linear Energy Transfer to the Formation and Resolution of DNA Repair Foci After Irradiation with Equal Doses of X-ray Photons, Plateau, or Bragg-Peak Protons

Abstract: Proton beam therapy is increasingly applied for the treatment of human cancer, as it promises to reduce normal tissue damage. However, little is known about the relationship between linear energy transfer (LET), the type of DNA damage, and cellular repair mechanisms, particularly for cells irradiated with protons. We irradiated cultured cells delivering equal doses of X-ray photons, Bragg-peak protons, or plateau protons and used this set-up to quantitate initial DNA damage (mainly DNA double strand breaks (DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 28 publications
5
37
0
Order By: Relevance
“…These observations are consistent with the described action of particles, including protons, that induce a direct DNA damage within their defined track and therefore tend to induce accumulated DNA damage in closer proximity [13,14,64,65]. It has been previously suggested that the high energy of particles, e.g., protons, strongly correlates with clustered DNA damage in the form of coalesced DNA DSB due to denser ionizing events [6,13,14,64,66]. Moreover, a prediction analysis done by a new computational track structure model which simulates complexity of DNA damage after proton irradiation, endorses our assumption of a more complex DNA damage induced by proton irradiation [67].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…These observations are consistent with the described action of particles, including protons, that induce a direct DNA damage within their defined track and therefore tend to induce accumulated DNA damage in closer proximity [13,14,64,65]. It has been previously suggested that the high energy of particles, e.g., protons, strongly correlates with clustered DNA damage in the form of coalesced DNA DSB due to denser ionizing events [6,13,14,64,66]. Moreover, a prediction analysis done by a new computational track structure model which simulates complexity of DNA damage after proton irradiation, endorses our assumption of a more complex DNA damage induced by proton irradiation [67].…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, we observed that irradiation with SOBP protons induced γH2A.X DNA foci-clusters, whereas DNA damage foci induced by X-ray photons were smaller and more randomly distributed over the whole nucleus. These observations are consistent with the described action of particles, including protons, that induce a direct DNA damage within their defined track and therefore tend to induce accumulated DNA damage in closer proximity [13,14,64,65]. It has been previously suggested that the high energy of particles, e.g., protons, strongly correlates with clustered DNA damage in the form of coalesced DNA DSB due to denser ionizing events [6,13,14,64,66].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations